2014
DOI: 10.1016/j.schres.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between suicide and violence in schizophrenia: Analysis of the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) dataset

Abstract: BackgroundSuicide and violence often co-occur in the general population as well as in mentally ill individuals. Few studies, however, have assessed whether these suicidal behaviors are predictive of violence risk in mental illness.AimsThe aim of this study is to investigate whether suicidal behaviors, including suicidal ideation, threats, and attempts, are significantly associated with increased violence risk in individuals with schizophrenia.MethodData for these analyses were obtained from the Clinical Antips… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 51 publications
5
32
0
1
Order By: Relevance
“…Another noteworthy finding of the CATIE study involved the relationship between violence, and suicidal threats and attempts in both males and female community-dwelling patients with schizophrenia. Witt, Hawton, and Fazel (2014) reported that past suicidal threats and attempts increased the rate of violent behavior in male schizophrenia patients by 3.8%, compared to a 2.8% increase in the non-suicidal group. In female patients, past suicidal threats and attempts raised the OR for violence to 9.4%, compared to a 4.4-fold increase in the non-suicidal patient group.…”
Section: State Versus Trait Factorsmentioning
confidence: 99%
“…Another noteworthy finding of the CATIE study involved the relationship between violence, and suicidal threats and attempts in both males and female community-dwelling patients with schizophrenia. Witt, Hawton, and Fazel (2014) reported that past suicidal threats and attempts increased the rate of violent behavior in male schizophrenia patients by 3.8%, compared to a 2.8% increase in the non-suicidal group. In female patients, past suicidal threats and attempts raised the OR for violence to 9.4%, compared to a 4.4-fold increase in the non-suicidal patient group.…”
Section: State Versus Trait Factorsmentioning
confidence: 99%
“…A score of 1 will from here on be referred to and analysed as suicidal ideation, a score of 2: suicide plans and 3: suicide attempt. This method of analysing suicide-data from the CDSS was applied in a similar manner in the CATIE-trial [56]. The PANSS Excitement Component (PANSS-EC) consists of the PANSS items P4 Hyperactivity, P7 Hostility, G4 Tension, G8 Uncooperativeness and G14 Poor Impulse Control.…”
Section: Assessmentsmentioning
confidence: 99%
“…Boter et al from the EUFEST study group have published data comparing the subgroup with comorbidities such as suicidality or substance use with participants without these comorbidities [7]. Witt et al have investigated the relationship between suicide and violence in the CATIE trial [56]. Brugnoli et al found previous suicidality, depressive symptoms, prolactin-related adverse events, male gender and history of hospitalisation for schizophrenia as risk factors for suicide or suicidal behaviours in the SOHO-study, but analysed positive psychotic symptoms only at a general level [8].…”
mentioning
confidence: 99%
“…Additional risk factors described by other authors include having a family history of suicide (Brent et al, 1996), certain genetic variations (Ben-Efraim et al, 2012), comorbid medical illnesses such as cancer or HIV (Cole et al, 2014; McManus et al, 2014); experiencing a social and/or financial crisis (Large et al, 2011) and having stressful life events (Pompili et al, 2011). Rates of suicidal behavior are significantly higher in psychiatric populations compared to the general population (Beghi et al, 2013), but most studies conducted so far have focused on specific psychiatric diagnoses such as bipolar disorder (Hauser et al, 2013), post traumatic stress disorder (PTSD) (Pompili et al, 2013), depression (Hawton et al, 2013), schizophrenia (Witt et al, 2014), borderline personality disorder (Soloff et al, 2014), anxiety disorders (Thibodeau et al, 2013), eating disorders (Suokas et al, 2014) and other diagnoses. On the other hand, relatively few studies have directly compared suicidal rates across different psychiatric disorders in a single patient sample.…”
Section: Introductionmentioning
confidence: 99%